Endotracheal intubation using a spiral endotracheal tube effectively reduces total tube handling time in children aged one month to six years using a McGrath video laryngoscope: a prospective randomized trial - Rahendra Rahendra; Fajar Sesario; Andi Ade Wijaya Ramlan; Raihanita Zahra; Christopher Kapuangan; Arif Hari Martono Marsaban; Aries Perdana (Anesthesia and Pain Medicine, 2024)
Background Airway management in children is challenging because of the smaller size, different proportions of anatomical structures compared to adults, and a higher risk of hypoxemia. Efforts to improve the efficiency of pediatric intubation can be made by manually twisting a spiral endotracheal tube (ETT) using a flexible stylet to manipulate its shape and angle. Methods This controlled trial randomized fifty children aged one month to six years who underwent elective surgery under general anesthesia into two groups (spiral ETT [sETT] and no-stylet ETT/standard ETT). The sETT was formed by twisting the ETT using a handmade tool. The primary objective was to determine the effectiveness of the sETT compared to the standard ETT in reducing intubation time. Secondary objectives were ETT placement accuracy, first-attempt intubation success rate, and adverse effects. Results The mean total tube handling time in the sETT group was significantly shorter compared to the no-stylet ETT group (sETT 16.8 ± 3.6 vs. standard ETT 18.8 ± 3.7 seconds; P = 0.049). sETT placement had a significantly greater central placement accuracy (odds ratio, 4.846; 95% confidence interval, 1.287-18.255; P = 0.015). However, first-attempt successful intubation rate (sETT 80% vs. standard ETT 64%, P = 0.208) and total intubation time (sETT: 46.5 ± 5.2 vs. standard ETT 48.4 ± 4.9 seconds; P = 0.205) were not significantly different. No adverse effects were observed for either ETT type. Conclusions Spiral ETT effectively reduces total tube handling time and improves ETT placement accuracy in children using video laryngoscopy.